PRODUKSI ASAM LAKTAT OLEH LACTOBACILLUS ACIDOPHILUS DALAM MEDIA FERMENTASI KOMBINASI LIMBAH CAIR TAHU DAN MANGGA (Mangifera indica l.) - Amir, Mellova; Sopiatunnisa, Neng; Abna, Inherni Marti (Faculty of Mathematic and Natural Science, Garut University, 2024)
Lactic acid is a hydroxycarboxylic organic acid used for various purposes and can be obtained through the fermentation of sugar from various sources. This research aimed to determine the ability of Lactobacillus acidophilus in a combination of tofu and mango waste to produce lactic acid using the fermentation method. Variations in media concentration for the combination of tofu and mango liquid waste are 0%, 25%, 50%, and 100% used with the basic fermentation media. The initial stage is the cultivation of L acidophilus, the growth curve, and then the fermentation process, determining the PH and levels of lactic acid produced using spectrophotometry. The research showed that L. acidophilus, combining tofu and mango liquid waste media, could produce lactic acid. Lactic acid levels in 0% combination media with 100% basic media were 2,040 mg/L, 25% combination media, 75% basic media, 2,081 mg/L, 50% combination media, 50% basic media, 2,316 mg/L, combination media 100 % of 2,440 mg/L. The highest levels of lactic acid were produced using a combination of 100% tofu and mango liquid waste at the 48th hour, amounting to 2,440 mg/L.